Analisis Pengaruh Pengembangan Karir dan Pengalaman Kerja Terhadap Produktivitas Kerja Karyawan Pada PT Sinde Budi Sentosa - Umar Usman; Ismi Mawadah (Mulia Pratama, 2023)
performance at PT. Sinde Budi Sentosa. This study uses quantitative methods of data collection techniques by giving questionnaires to respondents and interviewing related parties. The number of samples in this study were 50 respondents. The respondents are employees of PT. Sinde Budi Sentosa. Determination of this sample using the Slovin formula 10% of the population. Data were analyzed using multiple linear regression analysis, coefficient of determination analysis, t test and f test using SPSS version 26. The results showed that there was a positive influence between Career Development and Work Experience on employee work productivity at PT. Sinde Budi Sentosa. The results of multiple linear regression analysis Y = 21.350 + 0.493x1 + 0.027x2 means that if career development and work experience (X1 and X2 = 0) then employee work productivity is 21.350 and if career development and work experience (X1 and X2 = 1) then employee productivity employee work increased by 0.493 for X1 and 0.027 for X2. Based on the test results of the coefficient of determination (R2) = 52%. The results show that the work productivity of employees is influenced by Career Development and Work Experience by 52% and the rest is influenced by other factors not discussed in the study. The results of the partial test (t test) show that the results of the Career Development (X1) value on Employee Work Productivity (Y) show t count > t table of 3.799 > 1.677, so Career Development has an influence on employee work productivity. The results of testing the Work Experience variable (X2) on employee work productivity (Y) show t count < t table, the magnitude is 0.192 <1.677, so work experience has no effect on employee work productivity. Overall test results (f test) F count > F table (11.049 > 3.20) career development and work experience together have a positive and significant impact on employee work productivity.